Lexical Problems in Translation (Eurasian Research Bulletin, 2022)
The problems of translating foreign texts and vocabulary in any sector of the life is experiencing rapid development, as is the growing interest of users and developers in different terms itself. The primary and most pressing problem in working with a foreign text in this area is the choice of a suitable equivalent to a newly emerging concept. The key and most informative words that carry the main semantic load in the text of this topic are terms.